2015
DOI: 10.1080/17461391.2015.1073363
|View full text |Cite
|
Sign up to set email alerts
|

An occlusion paradigm to assess the importance of the timing of the quiet eye fixation

Abstract: The aim of the study was to explore the significance of the 'timing' of the quiet eye (QE), and the relative importance of late (online control) or early (pre-programming) visual information for accuracy. Twenty-seven skilled golfers completed a putting task using an occlusion paradigm with three conditions: early (prior to backswing), late (during putter stroke), and no (control) occlusion of vision. Performance, QE, and kinematic variables relating to the swing were measured. Results revealed that providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
3
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 49 publications
(76 reference statements)
3
37
3
2
Order By: Relevance
“…99.9 ms; Vine et al 2015). The early phase of the QE (QE-early) started at QE onset and ended with the initiation of the backswing.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…99.9 ms; Vine et al 2015). The early phase of the QE (QE-early) started at QE onset and ended with the initiation of the backswing.…”
Section: Methodsmentioning
confidence: 96%
“…the two-dimensional Euclidean distance between the top of the ball and the edge of the target; in cm) was recorded using a tape measure after each putt (Vine et al 2015). Error scores were then averaged (mean radial error) for each condition as a measure of performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They examined the quiet eye in different phases of the putt and found that, compared to missed putts, holed putts were characterized by a longer postmovement initiation quiet eye, whereas the premovement initiation quiet eye was not different. Second, Vine et al (2015) tested 27 experienced golfers (mean handicap 5.8) as they putted balls to a 10-ft (i.e., 3-m) distant hole. Participants' view of the ball was occluded either before or after movement initiation, through a liquid crystal glass panel-positioned above the ball-turning opaque.…”
Section: Quiet Eyementioning
confidence: 99%
“…These differences can be attributed to the task constraints, such as: different distances, and thus differing processing demands; aiming at a target, rather than a hole; and the use of truly novice participants, compared to skilled or less-skilled participants in other studies (Vickers 1992, 2004; Vine et al 2013, 2015). …”
mentioning
confidence: 99%